2012
DOI: 10.1515/jgt-2012-0003
|View full text |Cite
|
Sign up to set email alerts
|

Some skew linear groups with Engel's condition

Abstract: Abstract. Let D be a non-commutative division ring, m and n two natural numbers, M a maximal and N a subnormal subgroup of GL m .D/. In this paper, among other results, we show that: (1) if N is an n-Engel group, then it is central; (2) if m > 1 and M is locally nilpotent, then M is abelian; (3) if m > 1 and M is n-Engel, then the Hirsch-Plotkin radical of M is abelian. Also, we define some generalized Engel conditions on groups, and then we prove similar results, as quoted, for these groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Motivated by this result, several other authors examined various aspects of subnormal subgroups of D Ã , instead of the whole group D Ã . For example, it was shown that every subnormal subgroup of D Ã must be central in D if it is locally nilpotent, solvable, or n-Engel (see [13], [8], [10], respectively). Now, we consider the same problem in which the subnormal subgroup is assumed to be locally solvable.…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by this result, several other authors examined various aspects of subnormal subgroups of D Ã , instead of the whole group D Ã . For example, it was shown that every subnormal subgroup of D Ã must be central in D if it is locally nilpotent, solvable, or n-Engel (see [13], [8], [10], respectively). Now, we consider the same problem in which the subnormal subgroup is assumed to be locally solvable.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, they showed that if the cardinality of F is greater than 3α(w) 2 , then D = F . Recently, there are some articles on some subgroups of D * which satisfy a group identity or some special group identity (see [7,10,12,14]): Ramezan-Nassab and Kiani proved in [14] that subnormal subgroups of D * satisfying the n-Engel condition are contained in F . It is proved in [12] that every maximal subgroup of D * satisfying a group identity is the multiplicative group of a maximal subfield of…”
Section: Introductionmentioning
confidence: 99%
“…In all of those papers, authors attempted to show that the structure of maximal subgroups of GL n (D) is similar, in some sense, to the structure of GL n (D). For instance, if D is an infinite division ring, in [3] it was shown that every nilpotent maximal subgroup of GL n (D) is abelian, and in [13] the authors proved that for n ≥ 2, every locally nilpotent maximal subgroup of GL n (D) is abelian. Also, if D is non-commutative and n ≥ 2, in [2] it was shown that every soluble maximal subgroup of GL n (D) is abelian, and in [13] the authors proved that for n ≥ 3, every locally soluble maximal subgroup of GL n (D) is abelian.…”
Section: Introductionmentioning
confidence: 99%
“…Our object here is to discuss the general skew linear groups whose maximal subgroups are of some special types. Some properties of maximal subgroups of GL n (D) have been studied in a series of papers, see, e.g., [1,2,3,7,12,13]. In all of those papers, authors attempted to show that the structure of maximal subgroups of GL n (D) is similar, in some sense, to the structure of GL n (D).…”
Section: Introductionmentioning
confidence: 99%